"A change would do you good": Training medical students in Motivational Interviewing using a blended-learning approach – A pilot evaluation. Issue 4 (April 2019) - Keifenheim, K.E.; Velten-Schurian, K.; Fahse, B.; Erschens, R.; Loda, T.; Wiesner, L.; Zipfel, S.; Herrmann-Werner, A.
Highlights: Motivational interviewing curriculum for medical students investigated. MI can be successfully taught in a blended learning teaching format. Students are highly interested in learning MI. Students' baseline MI skills without specific training are moderate. Subjective and objective MI-related knowledge and skills improve. Abstract: Objectives This study aims to assess medical students' interest in a Motivational Interviewing (MI), the objective need for a special training, and students' satisfaction with and the effectiveness of such a course. Methods A mandatory MI course was implemented for sixth-semester medical students. Their interest in learning MI was evaluated, along with their satisfaction with the course, which was delivered in a blended-learning teaching approach. Participants' baseline MI skills and general communication skills were assessed. MI non-adherent behavior, like persuading and confronting patients, was noted. Successful learning was measured with a multiple-choice test administered before and after the course that assessed subjective knowledge and skills. Results Students were highly interested in learning MI. At baseline, they showed good communication skills but moderate MI skills. Satisfaction with the course was high. The course was effective, as subjective and objective knowledge and skills improved significantly. Conclusions This pilot study suggests that basic MI skills can be successfully taught in a blended-learning teaching approach. Further research should investigate sustainability and transfer to clinical practice. Practice implications Medical schools should consider providing students with special training in MI to help students counsel patients towards behavioral changes.